Multi-Omics Interdisciplinary Research Integration to Accelerate Dementia Biomarker Development (MIRIADE) - Mavrina, Ekaterina; Kimble, Leighann; Waury, Katharina; Gogishvili, Dea; Gómez de San José, Nerea; Das, Shreyasee; Coppens, Salomé; Fernandes Gomes, Bárbara; Mravinacová, Sára; Wojdała, Anna Lidia; Bolsewig, Katharina; Bayoumy, Sherif; et al. (Frontiers in Neurology, 2022)
Proteomics studies have shown differential expression of numerous proteins in dementias but have rarely led to novel biomarker tests for clinical use. The Marie Curie MIRIADE project is designed to experimentally evaluate development strategies to accelerate the validation and ultimate implementation of novel biomarkers in clinical practice, using proteomics-based biomarker development for main dementias as experimental case studies. We address several knowledge gaps that have been identified in the field. First, there is the technology-translation gap of different technologies for the discovery (e.g., mass spectrometry) and the large-scale validation (e.g., immunoassays) of biomarkers. Additionally, there is a limited understanding of conformational states of biomarker proteins in different matrices, which affects the selection of reagents for assay development. In this review, we aim to understand the decisions taken in the initial steps of biomarker development, which is done via an interim narrative update of the work of each ESR subproject. The results describe the decision process to shortlist biomarkers from a proteomics dataset to either develop immunoassays or mass spectrometry assays for Alzheimer’s disease, Lewy Body Dementia, and Frontotemporal Dementia. In addition, we explain the approach to prepare the market implementation of novel biomarkers and assays. Moreover, we describe the development of computational protein state and interaction prediction models to support biomarker development, such as the prediction of epitopes. Lastly, we reflect upon activities involved in the biomarker development process to deduce a best-practice roadmap for biomarker development.